Penguatan Komunikasi Kelembagaan dan Peningkatan Kapasitas Aparatur dalam Mewujudkan Pelayanan Publik Kolaboratif - Ferdyansyah Wicaksono; Taqwaty Firdausijah; Iwan Satibi; Ade Irawan; Yayu Purwati (Dharma: Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to strengthen collaborative public services through capacity building of public officials and enhanced communication among community institutions in Kelurahan Nyengseret, Bandung City. The program involved 80 participants, including village officials, neighborhood leaders, Posyandu cadres, youth organizations, and community empowerment institutions. The method employed collaborative training and mentoring through participatory discussions, reflective learning, case simulations, and focus group discussions. The results indicated improved understanding of service-oriented work culture, inter-institutional communication, and public service as a shared responsibility. Several strategic issues were identified, including limited human resources, increasing service demands, gaps between public expectations and service capacity, and insufficient integration of community institutions. The program outputs included a stronger service mindset, increased awareness of service consistency, and the utilization of community-based communication. The findings highlight that a collaborative public service approach is an effective strategy for improving sustainable service quality at the village level.